Fabrication and in vivo thrombogenicity testing of nitric oxide generating artificial lungs. Issue 12 (24th April 2013) - Amoako, Kagya A.; Montoya, Patrick J.; Major, Terry C.; Suhaib, Ahmed B.; Handa, Hitesh; Brant, David O.; Meyerhoff, Mark E.; Bartlett, Robert H.; Cook, Keith E.
<x xml:space="preserve">Abstract</x> Hollow fiber artificial lungs are increasingly being used for long‐term applications. However, clot formation limits their use to 1–2 weeks. This study investigated the effect of nitric oxide generating (NOgen) hollow fibers on artificial lung thrombogenicity. Silicone hollow fibers were fabricated to incorporate 50 nm copper particles as a catalyst for NO generation from the blood. Fibers with and without (control) these particles were incorporated into artificial lungs with a 0.1 m2 surface area and inserted in circuits coated tip‐to‐tip with the NOgen material. Circuits (N = 5/each) were attached to rabbits in a pumpless, arterio‐venous configuration and run for 4 h at an activated clotting time of 350–400 s. Three control circuits clotted completely, while none of the NOgen circuits failed. Accordingly, blood flows were significantly higher in the NOgen group (95.9 ± 11.7, p < 0.01) compared to the controls (35.2 ± 19.7; mL/min), and resistance was significantly higher in the control group after 4 h (15.38 ± 9.65, p < 0.001) than in NOgen (0.09 ± 0.03; mmHg/mL/min). On the other hand, platelet counts and plasma fibrinogen concentration expressed as percent of baseline in control group (63.7 ± 5.7%, 77.2 ± 5.6%; p < 0.05) were greater than those in the NOgen group (60.4 ± 5.1%, 63.2 ± 3.7%). Plasma copper levels in the NOgen group were 2.8 times baseline at 4 h (132.8 ± 4.5 μg/dL) and unchanged in the controls. This study demonstrates that NO generating gas exchange fibers could be a potentially effective way to control coagulation inside artificial lungs. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3511–3519, 2013.